Health-Related Quality of Life in Children with Acute Leukaemia and Central Nervous System Tumours: Current Evidence and Future Directions - Lyazat Manzhuova; Timur Saliev; Aigul Bazarbayeva; Maira Kabakova; Gulzhan Kashaganova; Aizhan Kudaibergenova; Zaure Dushimova (Children, 2026)
Remarkable advances in paediatric oncology over recent decades have transformed acute leukaemia and central nervous system (CNS) tumours from largely fatal diagnoses to conditions with survival rates exceeding 80% in many cases. This epidemiological success, however, has shifted the clinical and research focus toward survivorship and the long-term consequences of curative therapies. Health-related quality of life (HRQoL) has emerged as a critical outcome measure that captures the multidimensional impact of disease and treatment on children’s physical, psychological, social, and educational functioning. This review synthesises current evidence on HRQoL in children with acute leukaemias, particularly acute lymphoblastic leukaemia (ALL) and acute myeloid leukaemia (AML), and CNS tumours, the two most common childhood malignancies. We examine measurement approaches, disease-specific HRQoL patterns, comparative outcomes between diagnostic groups, biopsychosocial determinants, and emerging interventions. The evidence consistently demonstrates that while ALL survivors generally experience HRQoL comparable to or slightly below population norms, children with CNS tumours face substantially greater and more persistent impairments across multiple domains. Treatment-related factors, particularly cranial irradiation, neurocognitive sequelae, family functioning, and socioeconomic status emerge as key determinants.